Constitutional Politics in Europe: Continuing Trends in the Politics of Gender: Уставната политика во Европа: Тековни трендови во политиката на родот - Guerrina, Roberta; Trajanoski, Žarko (Identities: Journal for Politics, Gender and Culture, 2005)
Author(s): Roberta Guerrina | Роберта Гуерина Title (English): Constitutional Politics in Europe: Continuing Trends in the Politics of Gender Title (Macedonian): Уставната политика во Европа: Тековни трендови во политиката на родот Translated by (English to Macedonian): Žarko Trajanoski | Жарко Трајаноски Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 4, No. 1-2 (Summer - Winter 2005) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 9-35 Page Count: 24 Citation (English): Roberta Guerrina, “Constitutional Politics in Europe: Continuing Trends in the Politics of Gender,” Identities: Journal for Politics, Gender and Culture, Vol. 4, No. 1-2 (Summer - Winter 2005): 9-35. Citation (Macedonian): Роберта Гуерина, „Уставната политика во Европа: Тековни трендови во политиката на родот“, превод од англиски Жарко Трајаноски, Идентитети: списание за политика, род и култура, т. 4, бр. 1-2 (лето - зима 2005): 9-35.